Obituary: Joseph A. Buttigieg (1947-2019) - Mayo, Peter (International Gramsci Journal, 2023)
This is an obituary of Joseph A. Buttigieg by a long-time collaborator and friend of his, Professor Peter Mayo of the University of Malta, who apart from – and often overlapping with his Gramsci studies – carries out specialist research and teaching on educational matters.